Analysis Skin Temperature Distribution of Thermal Manikin. (May 2020) - Huda, L N; Indra,; Sentosa, W; Willyanto,
Abstract: Thermal Manikin is a human model designed for research and development in outdoor and indoor, military, and clothing environmental experiments. This research aimed to analyze the skin temperature distribution from Thermal Manikin. This study used Thermal Manikin which functions as a representative of the human body where the surface temperature of the body Thermal Manikin is made close to the surface temperature of the human body. The temperature of the Manikin Thermal skin was made constant at 34°C ± 1°C under stable room temperature conditions. Experiment was carried out with various air temperature conditions from 26°C to 32°C. Skin temperature measurements carried out on 24 body parts of Thermal Manikin for 90 minutes at 1-minute intervals. The measurement results obtained was then compared and analyzed at various air temperature conditions. The results of the analysis showed that the temperature of the skin in each part of the body's thermal Manikin was evenly distributed in each part of the body and the temperature of the body's skin thermal Manikin increases with the increasing air temperature around thermal Manikin.